ASPP2 Coordinates ERS-Mediated Autophagy and Apoptosis Through mTORC1 Pathway in Hepatocyte Injury Induced by TNF-α - Jia Yao; Hui Yang; Hui Yang; Han Wang; Honglin Shi; Honglin Shi; Yan Jiao; Yan Jiao; Ying Zhang; Ying Zhang; Dexi Chen; Dexi Chen; et al. (Frontiers Media S.A., 2022)
Background: Though ASPP2 plays an important role in regulating cell apoptosis and autophagy in case of liver injury, there remains a lack of clarity on the molecular mechanism of ASPP2 regulating autophagy and apoptosis.Methods: A hepatocyte injury model was constructed using HL7702 cell line and TNF-α. The cells were treated by ASPP2 overexpression adenovirus or short hairpin RNA lentivirus and endoplasmic reticulum stress (ERS) or the mammalian target of rapamycin (mTOR) inhibitor or agonist, respectively. The autophagy was detected by means of western blot and Green fluorescent protein-labeled- Microtubule-associated protein light chain 3 (GFP-LC3) plasmid transfection, while the apoptosis was detected through western blot, flow cytometry and TUNEL assay. Besides, the proteins related to ERS and mTOR were detected by western blot.Results: The low level of ASPP2 expression was accompanied by high-level autophagy and low-level apoptosis and vice versa in case of hepatocyte injury induce by TNF-α. By upregulating the proteins related to mTORC1 and ERS, ASPP2 induced apoptosis but inhibited autophagy. However, the effect of ASPP2 on autophagy and apoptosis can be reversed by the use of mTORC1 and ERS interfering agent, which indicates that ASPP2 regulated autophagy and apoptosis through mTORC1and ERS pathway. ERS treatment made no difference to the expression of ASPP2 and mTOR-related proteins, which suggests the possibility that the regulation of ERS on apoptosis and autophagy could occur in the downstream of ASPP2 and mTOR.Conclusion: ASPP2 could inhibit autophagy and induce apoptosis through mTORC1-ERS pathway in case of the hepatocyte injury induce by TNF-α. The role of ASPP2-mTORC1-ERS axis was verified in hepatocyte injury, which suggests the possibility that ASPP2 is an important regulatory molecule for the survival and death of hepatocyte.